The Socialisation of Gender Equality and LGBT Dangers to Build the Character of Elementary School Students with Integrity: Sosialisasi Kesetaraan Gender Dan Bahaya LGBT, Untuk Membentuk Karakter Siswa/I Sekolah Dasar Yang Terintegritas - Ronaldo Rahmadhano Siahaan; Muhammad Raihan; Khoirunnisa; Agustina Ningsih; Sunarno (Institute of Educational, Research, and Community Service, 2023)
With the rise of LGBT cases in Indonesia at the moment, especially in Riau Province, specifically in the city of Pekanbaru, which has recently become a very dangerous case and there must be action, prevention and education must also be provided from an early age. The target of this case is no longer adults but has spread to children, therefore it is not only the role of the city government but parents also play an important role in supervising children. One of the cases of Lesbian Gay Bisexual and Transgender (LGBT) was caught around a hotel in Sukajadi District some time ago. Through the UNRI KKN program, it is hoped that it can help parents and teachers in the process of educating students about the dangers of LGBT to students at SDN 116 Pekanbaru. This can be done by holding outreach regarding gender equality and also the dangers of LGBT to students so that they avoid LGBT cases and these cases will no longer become widespread.